2023
DOI: 10.1038/s41598-023-34584-z
|View full text |Cite
|
Sign up to set email alerts
|

The difference in the cellular uptake of tocopherol and tocotrienol is influenced by their affinities to albumin

Abstract: Vitamin E is classified into tocopherol (Toc) and tocotrienol (T3) based on its side chains. T3 generally has higher cellular uptake than Toc, though the responsible mechanism remains unclear. To elucidate this mechanism, we hypothesized and investigated whether serum albumin is a factor that induces such a difference in the cellular uptake of Toc and T3. Adding bovine serum albumin (BSA) to serum-depleted media increased the cellular uptake of T3 and decreased that of Toc, with varying degrees among α-, β-, γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The stability of curcumin can be affected by nanoformulation, e.g., when encapsulated into vesicles of soy lecithin of about 100 nm in diameter, wherein a synergistic effect of concentration and confinement was observed as a result of keto to enol tautomerization [ 14 ]. Furthermore, once in circulation, curcumin may become stabilized by binding to serum albumin that may, similarly to vitamin E, facilitate its transport across the vasculature into tissues and cells [ 7 , 49 , 50 ]. Curcumin is more stable in a cell culture medium containing 10% fetal calf serum as well as in human blood; 50% of curcumin is still intact after 8 h of incubation [ 25 ].…”
Section: Curcumin and Curcuminoidsmentioning
confidence: 99%
“…The stability of curcumin can be affected by nanoformulation, e.g., when encapsulated into vesicles of soy lecithin of about 100 nm in diameter, wherein a synergistic effect of concentration and confinement was observed as a result of keto to enol tautomerization [ 14 ]. Furthermore, once in circulation, curcumin may become stabilized by binding to serum albumin that may, similarly to vitamin E, facilitate its transport across the vasculature into tissues and cells [ 7 , 49 , 50 ]. Curcumin is more stable in a cell culture medium containing 10% fetal calf serum as well as in human blood; 50% of curcumin is still intact after 8 h of incubation [ 25 ].…”
Section: Curcumin and Curcuminoidsmentioning
confidence: 99%
“…Moreover, the cellular uptake and distribution of Tocs and tocotrienols are different 123) . The Nakagawa group recently demonstrated that Tocs and tocotrienols exhibit varying affinities for albumin, which could potentially lead to differences in their cellular uptake 124) . These reports suggest the significance of the structure and types of binding proteins in determining the intracellular localization of VE.…”
Section: Effect Of Ve On Organelles Related To Ferroptosismentioning
confidence: 99%